Role of Oxidative Stress in Various Stages of Psoriatic Patients - Khan, Feroz; Akram, Muhammad; Rehman, Azizur; ., Mehreen; ., Jahanzaib; Naeem, Syed Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To Assess the Role of Antioxidant, Lipid Peroxidation Status and Lipid Profile in various stages of Psoriasis Patients. Methodology: The present study was a Case Control. It was carried out in the Department of Biochemistry, at Basic Medical Sciences Institute (BMSI) Jinnah Post Graduate Medical Centre from April - December 2015. One hundred and twenty cases of psoriasis patients grouped as Mild, Moderate, Severe and Forty healthy control for comparison was included in the study. Lipid Profile including serum total cholesterol, Triglyceride (TG), - high density lipoproteins (HDL) and low- density lipoproteins (LDL), were estimated by enzymatic colorimetric Method on Micro lab 300 (Merck & Germany) and Antioxidant status like Superoxide Dismutase (SOD) and Lipid Peroxidation status like Malondialdehyde (MDA) were measured by ELISA. The statistical analysis was performed by SPSS software Version 16. P value less than 0.005 was considered significant. Results: Our result showed significantly increase in the mean serum level of triglycerides (TG), Total Cholesterol and low density lipoproteins in psoriatic patients when compared to control where as high density Lipoproteins was significantly decline in psoriatic groups when compared to control while SOD level was reduced in psoriasis patients as compared to control. The MDA level was raised in psoriasis patients as compared to control. Conclusion: The finding of our study support the hypothesis that imbalance in oxidant-antioxidant system play role in the etiology of psoriasis. Also dyslipidemia was observed risk factor for development of cardiovascular diseases. Keywords: Oxidative Stress, Psoriasis